A method for isolation, purification and transient transformation of mesophyll protoplasts from tulip (Tulipa gesneriana)(郁金香叶肉原生质体的分离纯化与瞬时转化方法) - 霍信屹(HUO Xinyi); 陈欣晨(CHEN Xinchen); 赵慧敏(ZHAO Huimin); 向林(XIANG Lin); 产祝龙(CHAN Zhulong); 王艳平(WANG Yanping) (浙江大学学报. 农业与生命科学版)
Protoplast isolation and purification are influenced by plant genotype and extraction conditions. Establishing a system for the isolation, purification, and transient transformation of tulip (Tulipa gesneriana)protoplasts is an effective way to explore the mechanism of tulip growth and development and conduct studies of somatic cell fusion. In the present study, we established a polyethylene glycol-calcium ion (PEG-Ca2＋) mediated transient transformation system for tulip protoplasts by the leaves of the tulip variety ‘Dow Jones’, which depended upon comparisons of different pre-treatments of leaves, osmotic pressures, and enzymatic hydrolysis durations. The results showed that the most suitable material for protoplast extraction was 3-week-old leaves. The middle part of each leaf was cut into 1.0 cm×2.0 cm pieces and then the upper and lower epidermis of the leaf pieces were peeled off. The enzymatic mixture was composed of 1.5% cellulase R-10, 0.75% macerozyme R-10, 10 mmol/L 2-morpholinoethanesulphonic acid (pH=5.7), 0.4 mol/L D-mannitol, 20 mmol/L KCl, 10 mmol/L CaCl2, 0.1% bovine serum albumin and 1.5 mmol/L β-mercaptoethanol. The optimal enzymatic hydrolysis duration was 6 h. Under the optimal extraction conditions, there ware certain differences in protoplast yield among different varieties. The protoplast yield of ‘Dow Jones’ was greater than that of ‘Verandi’ and ‘World’s Favorite’, with 8.05×105 protoplasts per gram of fresh leaves. The p35S::GFP vector was transfected into ‘Dow Jones’ protoplasts using PEG-Ca2＋ mediated transient transformation, and the expression of green fluorescent protein was observed using confocal laser scanning microscope, with a transformation efficiency of 33.2%. This study provides new technical support for the functional research on tulip genes and the cultivation of new varieties. . 原生质体的分离和纯化受植物基因型和提取条件等因素的影响。建立郁金香原生质体的分离纯化与瞬时转化体系，是解析郁金香生长发育机制和开展体细胞融合的有效途径之一。本研究以郁金香品种‘Dow Jones’叶片为试验材料，通过比较叶片的不同处理方式、渗透压大小和酶解时间等因素的影响，建立了基于聚乙二醇-钙离子（polyethylene glycol-calcium ion, PEG-Ca2＋）介导的郁金香原生质体瞬时转化方法。结果表明：原生质体提取的最适材料为3周龄叶片，选取叶片中间部位切成1.0 cm×2.0 cm大小并撕去上下表皮，酶解条件为1.5%纤维素酶R-10、0.75%离析酶R-10、10 mmol/L 2-吗啉乙磺酸（2-morpholinoethanesulphonic acid, MES；pH=5.7）、0.4 mol/L D-甘露醇、20 mmol/L KCl、10 mmol/L CaCl2、0.1%牛血清白蛋白（bovine serum albumin, BSA）、1.5 mmol/L β-巯基乙醇，最佳酶解时间6 h。在最佳提取条件下，不同品种之间原生质体提取效率存在一定差异，‘Dow Jones’叶片的原生质体得率高于‘Verandi’和‘World’s Favorite’，每克鲜叶可得到原生质体8.05×105个。利用PEG-Ca2＋介导的瞬时转化法将p35S::GFP载体导入郁金香原生质体，在激光共聚焦扫描显微镜下观察到绿色荧光蛋白的表达，‘Dow Jones’品种的转化效率为33.2%。以上结果为郁金香基因功能研究和新品种培育等提供了新的技术参考。